SUN1 silencing inhibits cell growth through G0/G1 phase arrest in lung adenocarcinoma - Huang, Weiyi (Onco Targets Ther, 2017)
PURPOSE: Cytoskeleton is critical for carcinoma cell proliferation, migration, and invasion. Sad-1 and UNC-84 domain containing 1 (SUN1) is one of the core linkers of nucleoskeleton and cytoskeleton. However, the functions of SUN1 in lung adenocarcinoma are largely unknown. METHODS: In this study, we first transduced the lentivirus delivering the short hairpin RNA (shRNA) against SUN1 to lung adenocarcinoma cells (A549 and 95D cells) with high efficiency. After lentivirus infection, quantitative real-time polymerase chain reaction and Western blotting were used to detect the expressions of SUN1 mRNA and protein. The cell proliferation and colony formation were detected by MTT assay and colony formation assay, respectively. The cell distribution in the cell cycle was analyzed by flow cytometry. RESULTS: Both mRNA and protein levels of SUN1 were significantly decreased in A549 and 95D cells after lentivirus infection, as indicated by quantitative real-time polymerase chain reaction and Western blot. Next, we found that cell proliferation and colony formation were markedly reduced in SUN1 silenced cells. Moreover, suppression of SUN1 led to cell cycle arrest at G0/G1 phase. Furthermore, Cyclin D1, CDK6, and CDK2 expressions were obviously reduced in A549 cells after SUN1 silencing. CONCLUSION: These results suggest that SUN1 plays an essential role in proliferation of lung adenocarcinoma cells in vitro and may be used as a potential therapeutic target for the treatment of lung adenocarcinoma in the future.